Történelmi beágyazódottság és régiófejlődés : Lengyelország területi megosztottsága - Schmidt, Andrea (Közép-Európai Közlemények, 2011)
The essay deals with the territorial disparities of Poland and the new aspects of regional development. According to the general opinion, there are two types of explanation of the differences of the level of regional development. According to the evolutionist perception, the roots of the regional differences are the consequents of the cleavages coming from the historical past. On the other hand, the other opinion is based on the ’big bang’ of the economic and political transformation. There are different perceptions of the phenomenon ’region’, some of the authors concentrate on the regional identity and the region as a historical phenomenon. The regions have different historical past in the Central and Eastern European countries where the role of the central government had greater influence. Finally, the essay deals with the cleavages of Poland and the several approaches made in oreder to eliminate these differences, and the role of the regional development programmes and practices.